2018
DOI: 10.1039/c8cp04253e
|View full text |Cite
|
Sign up to set email alerts
|

Unveiling CO adsorption on Cu surfaces: new insights from molecular orbital principles

Abstract: A holistic analysis of adsorption energies, charge transfer, and structural changes has been employed to highlight the variations in adsorption mechanisms upon changing the surface type and the adsorption site.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
47
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(56 citation statements)
references
References 36 publications
9
47
0
Order By: Relevance
“…SAA and pure metal surfaces, whereon surface atoms have a coordination number of 8. We plot DFT calculated Eads(CO) on (100) SAA and pure metal surfaces inFigure 4(a) and we find that our computed values of Eads(CO) on Cu(100) and Ni(100) are in agreement with other DFT using RPBE and experimental studies 60,61. Pt SAAs Pd SAAs Rh SAAs Ir SAAs Ni SAAs-3…”
supporting
confidence: 77%
“…SAA and pure metal surfaces, whereon surface atoms have a coordination number of 8. We plot DFT calculated Eads(CO) on (100) SAA and pure metal surfaces inFigure 4(a) and we find that our computed values of Eads(CO) on Cu(100) and Ni(100) are in agreement with other DFT using RPBE and experimental studies 60,61. Pt SAAs Pd SAAs Rh SAAs Ir SAAs Ni SAAs-3…”
supporting
confidence: 77%
“…This finding is in line with the previous reports [16,21,22]. Although the trend and the preferred adsorption site agrees with the experimental data, previous studies reported Eads changing between ~80 kJ/mol at low coverage (< 0.2 ML) to ~50 kJ/mol around saturation coverage (~0.55 ML) [5,9,17,[23][24][25]35]. The computed value of 135 kJ/mol (for 0.22 ML) and ~90 kJ/mol (for 0.50 ML) appear to be overestimated.…”
Section: Resultssupporting
confidence: 93%
“…However, this kind of a mismatch is expected considering the temperature-pressure gap between the experiments and the DFT simulations (0 K, 0 bar). On the other hand, reported Cu-C and C-O bond lengths of 1.90 ± 0.1 Å and 1.15 ± 0.1 Å [11,35,36], are in perfect agreement with the produced data, especially with on-top adsorption at θCO = 0.50 ML, where most of the previous experimental data is produced.…”
Section: Resultssupporting
confidence: 86%
“…These copper states can offer chemically labile empty orbitals for accepting electrons from CO's 5σ molecular orbitals, as shown in the inset, and facilitate the chemisorption of CO molecules on the Cu-rich areas of the surface. 76,77…”
Section: Structural Characterization In Operandomentioning
confidence: 99%